Music-Assisted Training for Dart Throwing Novices: Post-Training Effects on Heart Rate and Performance Accuracy. Issue 1 (February 2022) - Tso, Ivor T. H.; Law, James C. L.; Wong, Thomson W. L.
While previous research has suggested that lowering athletes' heart rates can enhance sports performance, it is unknown whether slow-paced music might induce a lower heart rate and thereby improve some types of motor performance. In this study, we investigated the effects of different types of music during dart-throw training on both heart rate and dart-throwing performance in 45 ( M age = 19.7, SD = 0.31 years) novice dart throwers who were randomly assigned to either a Slow Music Group (SMG), a Fast Music Group (FMG), or a Control Group (CG). All participants completed three dart-throwing blocks - Pre-Test, Practice, and Post-Test. During the Practice block, participants practiced dart-throwing with either slow-paced, fast-paced or no music according to their assigned group. We recorded the participants' heart rates and total dart-throwing accuracy scores during Pre-Test and Post-Test. Music-assisted dart-throw training with slow-paced music was effective in significantly inhibiting a performance-related increase in heart rate and was associated with the greatest dart throwing improvement after training.